Tuberous sclerosis complex: a case report - Poolakundan, Harris; Jenner, Feroz P.; Kharim, Abdul; Vijayalekshmi, S.; Sasidharan, Anjana (International Journal of Research in Medical Sciences, 2017)
Tuberous Sclerosis Complex is an autosomal dominant phakomatosis. This neurocutaneous disorder usually presents with seizures, facial angiofibroma and mental retardation (Vogt’s triad). Here we report a case where a 25 year old gentleman presented with recurrent seizures, and was diagnosed to have tuberous sclerosis complex.